1976
DOI: 10.1530/jrf.0.0460189
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of plasma-derived proteins at much lower concentrations in the uterine lumen of the rabbit: a kinetic study of passage

Abstract: Human serum albumin (HSA) and human gamma globulin (HGG) in serum and uterine fluid of nonpregnant rabbits at various times after an i.v. injection (100 mg/kg) were measured by a radial immunodiffusion test using specific antisera. The HSA concentration in uterine fluid rose to a peak at 12 hr when it was 11% of the serum concentration and then declined, whereas HGG reached a peak at 18 hr (3\m=.\2% of serum level) and decreased thereafter. The HSA passed 2\ m=1/ 2\ times faster than HGG, but both proteins equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

1977
1977
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Previous studies have indicated that about 90 % of the macromolecules in the uterine fluids of nonpregnant females are derived from plasma in the rabbit (Kulangara, 1976) and the rat (Ringler, 1961), but the present results do not confirm this for the rat. This study defines qualitative and quantitative differences between the uterine luminal proteins and serum of the rat and shows that the endocrine state of the females is associated with marked changes in the macromolecular composition of the uterine fluids.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have indicated that about 90 % of the macromolecules in the uterine fluids of nonpregnant females are derived from plasma in the rabbit (Kulangara, 1976) and the rat (Ringler, 1961), but the present results do not confirm this for the rat. This study defines qualitative and quantitative differences between the uterine luminal proteins and serum of the rat and shows that the endocrine state of the females is associated with marked changes in the macromolecular composition of the uterine fluids.…”
Section: Discussioncontrasting
confidence: 99%
“…Comparison of in situ hybridization patterns at these stages (Figs 4A and 5A) suggests that only the more superficial epithelial cells contain GP42 message in the PSP uterus. We are not aware of other reports indicating possible blastocyst-induced alterations in rabbit endo¬ metrial glycoprotein secretion during the periimplantation period, although conceptus effects on the epithelial glycocalyx (Anderson & Hoffman 1984) and stromal-vascular prostaglandin synthesis (Hoffman et al 1984) Kulangara 1976). That GP42 is not of vascular origin was suggested by the demonstration of immunoreactive GP42 in the serum-free medium from epithelial cells isolated on day 4 PSP and cultured for four days (Hoffman et al 1996).…”
Section: Discussionmentioning
confidence: 96%